Development of Digital Teaching Materials for Imaginative Stories Based on Ethnoliteracy for Indonesian Language Learning in Elementary Schools - Nurani, Riga Zahara; Chandra, Deni; Julistiana, Risma; Salimi, Moh; Ruuhwan, Ruuhwan; Zainnuri, Hasan (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to develop valid, practical, and effective ethnoliteracy-based digital teaching materials for imaginative story learning in elementary schools. The research employed a Research and Development (R&D) method using the 4D Thiagarajan model, consisting of the definition, design, development, and dissemination stages. The participants included fifth-grade students in Tasikmalaya Regency, teachers, and expert validators in language, content, and media. Data were collected through tests, questionnaires, interviews, observations, and documentation, and analyzed using qualitative and quantitative techniques. The needs analysis indicated a strong demand for digital teaching materials among teachers (94.7%) and high student interest in digital media (92.6%) and visual illustrations (90.8%). Expert validation scores demonstrated that the product was feasible in terms of language (3.4), content (3.4), and highly feasible in media design (3.6). Field trials showed that the digital teaching materials were practical, engaging, and enhanced students’ imaginative story-writing abilities and ethnoliteracy understanding. The effectiveness was reflected in the improvement of students’ average scores from 70.34 (pretest) to 81.45 (posttest), with an average N-Gain of 0.40 categorized as moderate. Overall, the ethnoliteracy-based digital teaching materials are feasible and effective as an innovative resource for Indonesian language learning and contribute to strengthening students’ cultural identity in the digital era.